Terminology-Based Indonesian Language Teaching Materials Development: ISTIQLAL High School Context - Susy Deliani; Edi Yanto ML; Al Kausar Lingga; Hakim Prasasti Lubis; Enda Tarigan; Nunung Susilo Putri (REiLA : Journal of Research and Innovation in Language, 2019)
This exploratory study aims to describe (1) the development of terminology-based Indonesian language materials for students in Deli Serdang, (2) the level of validation of terminology-based Indonesian language materials for students in Deli Serdang, (3) students' responses related to the legibility of terminology-based Indonesian language materials. The subjects of this study were content experts, Indonesian language subject teachers, and students of ISTIQLAL High School Deli Serdang. The procedure of this study adapted research procedures from Borg and Gall. The instruments used for data collection in this study were documentation, observation, questionnaires and interviews. Data analysis techniques applied in this study were qualitative and quantitative techniques. The results of this study indicate that: (1) teaching materials are designed in line with the 2013 curriculum based on terminology, (2) the level of validation of teaching materials is in good qualification, and (3) the response of users of teaching materials in the field test phase is good.